PELATIHAN SERTIFIKASI DALAM MEWUJUDKAN PEMBIMBING HAJI PROFESIONAL: IKHTIAR MEMBERIKAN PELAYANAN PRIMA BAGI JAMAAH HAJI INDONESIA - Mutrofin; Harianto, Budi; Santoso, Bobby Rachman; Rohmat; Ni'amah, Luthfi Ulfa; Nurcholis, Ahmad; Susilo, Edi; Khoiruddin, Ahmad (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The implementation of the hajj pilgrimage involving millions of pilgrims every year requires excellent service, especially from the aspect of worship guidance. In the context of Indonesia as the largest hajj pilgrim sending country in the world, the existence of professional and competent hajj guides is an urgent need. This study aims to examine the role of certification training in forming professional hajj guides who are able to provide excellent service to pilgrims. Through a descriptive qualitative approach and case studies, it was found that certification training organized by the Ministry of Religion of the Republic of Indonesia is a strategic instrument in increasing the capacity, competency standards, and accountability of hajj guides. Certification includes scientific aspects, communication skills, and management of the hajj pilgrimage in accordance with sharia and applicable regulations. The results of the study show that supervisors who have participated in training and obtained certificates tend to have better service quality, are able to guide pilgrims effectively, and contribute to the smooth implementation of the hajj as a whole. Therefore, certification training is not just an administrative formality, but an important part of a systematic effort in realizing superior hajj services and oriented towards pilgrim satisfaction.